Biological activities and chemical composition of essential oil of Achillea maritima (L.) Ehrend. & YPGuo - Elkiran, Omer; Avsar, Cumhur; Bagci, Eyup (Taylor & Francis Inc, 2023)
This study aimed to describe the chemical composition of the essential oil (EO) of stems, leaves and flowers of A. maritima collected from Turkey, and verify its antimicrobial and antioxidant properties. The EO was analyzed by GC-FID and GC-MS. Fifty-nine compounds representing to 98.1% of the EO were identified. The antimicrobial activities were determined against seven bacteria and two yeast species by using disc diffusion and MIC techniques. According to the results, it was observed that there was no effect of the EO against Gram-positive bacteria. The EO showed a low effect (8-9 mm) against Gram-negative bacteria, but the EO had a high effect (20-22 mm) against the tested fungi. In addition, according to the MIC test results, the EO presented effects against C. krusei, C. parapsilosis at a concentration of 50 mu l/ml. The antioxidant activity of the EO was determined as IC50 = 31.9 mu l/mL.
Keywords: Achillea maritima; essential oil; yomogi alcohol; antimicrobial activity; antioxidant activity